Violation of the Convention on the Elimination of All Forms of Violence Against Women: A Case of Flagrancy in Kisangani City (Tshopo Province), DR Congo - Modeste Ndaba Modeawi; JP Ndolete Geregbia; Gédéon Ngembomba Bindo; Jean-Paul Koto-Te-Nyiwa Ngbolua; Monizi Mawunu (Abdul Media Literasi, 2024)
The Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) imposes on signatory States the obligation to implement and apply legal measures promoting equality and the elimination of gender discrimination. The General Assembly adopted it in 1979. Violence against women is, on the one hand, one of the most systematic and widespread forms of human rights violation in the world and, on the other, a socio-economic problem that impacts social harmony, economic growth and threatens overall development progress. The consequences include the deterioration of women’s mental and physical health, disruption of communities, and a decrease in economic productivity. The manifestation of unequal power relations between women and men is one of the most extreme forms of gender-based discrimination and an attack on the dignity and fundamental rights of women and girls. Gender-based violence stems from structural causes linked to the norms and values of a society, culture, or community. These factors legitimize and perpetuate various gender inequalities based on a hierarchy of relationships between men and women, thus contributing to gender-based violence. Harmful stereotypes and traditional expectations further bolster these inequalities, restricting women's autonomy and frequently rationalizing acts of violence. At the beginning of October 2023, a woman was subjected to cruel and degrading treatment, tied up and beaten by law enforcement officers in Kisangani, the capital of Tshopo province, on the orders of her ex-husband; the latter, using his position as a public official, ordered the arrest and beating of his ex-wife by law enforcement officers; As a result, the person who gave the order and the officers who carried out the manifestly illegal order were prosecuted and convicted, in accordance with the Declaration on the Elimination of Violence against Women, which requires States to act with due diligence to prevent, investigate and punish acts of violence against women in accordance with national law, whether perpetrated by the State or by private persons. Every woman has the right to respect for the inherent dignity of the human person and to recognition and protection of her human and legal rights. This article is timely and calls for the unfailing application of provisions on respect for the recognised rights of women and girls, in the interests of a fairer and more balanced society.